Specialised pro-resolving mediators of inflammation in inflammatory arthritis. (April 2016) - Barden, Anne E.; Moghaddami, Mahin; Mas, Emilie; Phillips, Michael; Cleland, Leslie G.; Mori, Trevor A.
Abstract: Introduction: Specialised pro-resolving mediators (SPM) are derived from n-3 long chain polyunsaturated fatty acids (n-3FA). They promote resolution of inflammation and may contribute to the beneficial effects of n-3FA in patients with arthritis. This study compared SPM in knee effusions and plasma of patients with arthritis taking n-3FA, and plasma of healthy volunteers taking n-3FA. Methods: Thirty six patients taking n-3FA undergoing arthrocentesis for an inflammatory knee effusion and 36 healthy volunteers who had taken n-3FA (2.4 g/day) for 4 weeks were studied. SPM in synovial fluid and plasma were measured by liquid chromatography-tandem mass spectrometry included 18-hydroxyeicosapentaenoic acid (18-HEPE), the precursor of the E-series SPM (RvE1, RvE2, RvE3, 18R-RvE3), and 17-hydroxydocosahexaenoic acid (17-HDHA), the precursor of the D-series SPM (RvD1, 17R-RvD1, RvD2). Other SPM included protectin D1 (PD1), 10S, 17S-dihydroxydocosahexaenoic acid (10, 17S-DHDHA), maresin-1 (MaR-1) and 14-hydroxydocosahexaenoic acid (14-HDHA) derived from docosahexaenoic acid (DHA). Results: E- and D-series SPM and the precursors 18-HEPE and 17-HDHA were present in synovial fluid and plasma of the patients with inflammatory arthritis. Plasma SPM were negatively related to erythrocyte sedimentation rate in arthritis patients ( P <0.01) and synovial fluid RvE2 was negatively associated with pain score ( P =0.02). Conversion from 18-HEPE and 17-HDHA to E- and D-series SPM was greater in synovial fluid ( P <0.01). Most plasma SPM in arthritis patients were elevated ( P <0.05) compared with healthy volunteers, and conversion to E- and D-series SPM was greater ( P <0.01). Conclusions: SPM are present in chronic knee effusions and although the levels are lower than in plasma, the association between synovial fluid RvE2 and reduced pain scores suggests that synthesis of SPM at the site of inflammation is a relevant mechanism by which n-3FA alleviate the symptoms of arthritis. Highlights: Plasma SPM are elevated in arthritis compared with controls taking n-3FA. Conversion to E- and D-series SPM was greater in SF than plasma of arthritis patients. Synovial fluid RvE2 was negatively associated with pain score in arthritis patients.